Children’s perspectives on sugary snacks through elicitation techniques – repertory grid and generative method - Liang, Linglin; Yu, Yue (Frontiers in Psychology, 2025)
BackgroundSugary snacks are prevalent in children’s daily lives and may impact their diet positively or negatively, yet few studies explore children’s perceptions and attitudes of these foods from their daily experiences in China.AimsThis study aims to (i) assess children’s perceptions and attitudes of sugary snacks and (ii) compare two child-centered elicitation techniques—Repertory Grid Technique (RGT) and Generative Method (GM)—based on Personal Construct Theory (PCT).MethodsA qualitative study was conducted with 31 children (6–10 years old) in Hangzhou and Fuzhou, China. Children participated in RGT (dichotomous comparisons using product cards) and GM (creative expression through drawing/clay) in one-on-one sections. The output of the task was analyzed for thematic analysis and descriptive statistics.ResultsThemes identified included sensory, packaging, interaction, emotion, cognition, and socio-culture. Children expressed concern about food composition and showed limited understanding of sugar’s functions and cultural significance. The RGT elicited more product attributes (358 vs. 190 in GM), with a significant difference (p < 0.001). RGT generated a balanced mix of concrete and abstract attributes, while GM elicited more abstract attributes.ConclusionThe findings highlight that children can be educated about the formulation and cultural aspects of sugary snacks. Encouraging richer “in-mouth” and “in-body” interactive education could be beneficial. Adopting a child-centered approach fosters engaging conversations. RGT efficiently inspires children to generate both concrete and abstract product attributes and is easy to understand but less enjoyable. On the other hand, GM tends to generate more abstract and novel ideas that strongly reflect children’s preferences. However, it requires more time and cognitive effort to understand, though it maintains a higher level of enjoyment and engagement. Understanding these findings aids in developing nutrition education that captivates and engages children. Insights into elicitation techniques can guide researchers seeking to understand children’s perspectives effectively.